Aplicación de la estrategia "Aprendemos Jugando" en el aprendizaje del Área Lógico Matemática en niños de cuatro años de edad de la Institución Educativa N° 305 del caserío de Monterrey del distrito de Nueva Cajamarca. Rioja, 2007 - Edquen Tapia, Merly Janet (2009)
This research work was the implementation of the strategy "learn by playing," on leaming of Mathematics in Logical Area boys and girls four years of age by school No. 305 of Monterrey Cathedral in the District of New Cajamarca. The problem erase because of the experience gained during the development of our professional practices, where there were sorne shortcomings in terms of learning, especially Logical Area Mathematics. In this sense, it was proposed to implement a systematic strategy that will help improve the learning of children, causing the overall objective of this investigation. On the operational side, a total of 25 boys and girls to whom they were initially evaluated to verify that state entering the experiment, which was contrasted with the implementation of the post. it is assumed that these results would be better to the start, because the children were encouraged by the Game for the first 3 months of the application. This assumption was the basic assumptions of inquiry, whose constrastación was done with the student t test for paired difference. In terms of results, we worked with in the margin of error of 5%, that is, it is hoped that in 95 out of 100 cases with the implementation of the strategy "learn by playing," improved learning in terms of representation graphic and interpretation of collections of objects using conventional and unconventional codes, recognize quantities of objects from a collection of up to 5 and in a progressive manner, organization and implementation of various measures to resolve problem situations, interpretation and creation of sets of objects according an approach and argumentation, among other logical far the Area Mathematics. Finally, the results of the investigation, being conducted under a design and preexperimental unable to perform the corresponding scrambling, have only a local but you can specify that in similar contexts implementing the strategy provides significant results.